Pengaruh World Trade Organization (WTO) Terhadap Globalisasi Dalam Peranan Hukum Di Indonesia - Veri Mei Hafnizal (Puslatbang KHAN, 2018)
Basically the interests and policies of Indonesia towards international agreements, especially in the trade sector is not independent and following their domestic interests. It has an impact on the development of Indonesian law which must prepare for competition in free trade. The method of analysis used juridical normative analysis which is to study secondary data and literature study. The results explain that law is needed to regulate all aspects of economic activities. It has an impact on the development of Indonesian law which must prepare to face competition in free trade. In the other side, the increasing relation of economic law and legal globalization it makes the development of law in Indonesia was growing and move into economic globalization. One of steps to anticipate globalization is giving the authority to state in order to perform its function as controlling the market through various economic regulations. To consider, it can be said that the government does not prepare its people in the face of a free trade in terms of law to protect the people. However, the development of economic law cannot protect the people as a whole.